Ethical Challenges to Determination Brainstem Death in Intensive Care and Its Medicolegal Aspects: A Case Report - Kulsum Kulsum; Taufik Suryadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
A 21-year-old female patient treated in the Intensive Care Unit (ICU) due to a traffic accident, after two days of treatment was declared brainstem death, the patient's family asked the doctor to continue treatment efforts in the hope of improving the patient's condition. The team of doctors differed in response to the patient's family request. Doctor A said that brain stem death meant that the patient had died and that no further action was needed, but Doctor B was of the opinion that the medical indications were absent but needed to provide an opportunity for the patient's family to see the patient's condition until he could eventually die naturally. According to doctor B it is not easy to determine brain stem death because it has several ethical and medicolegal consequences such as termination of life assistance, a certificate of brain stem death, and post-brain stem death organ transplantation. The medical decision taken is to keep the patient in care and after 3 days the patient is declared dead.